Characterization of novel stress degradation products of Bempedoic acid and Ezetimibe using UPLC-MS/MS: development and validation of stability-indicating UPLC method - Anuradha Vejendla; Subrahmanyam Talari; G. Ramu; Ch Rajani (SpringerOpen, 2021)
Abstract Background A receptive and easily comprehended technique was evolved for simultaneous assessment of Bempedoic acid and Ezetimibe and its impurities characterized by UPLC-MS/MS. Results This technique involves chromatographic separation with a C18 column of water symmetry (150 mm × 4.6 mm, 3.5 µm). A mobile phase of 0.1% OPA (orthophosphoric acid) and acetonitrile in 50:50 v/v with 1 mL/min flow rate and ambient temperature was used. UV observation was taken at 230 nm. The recoveries, linearity, and quantification limits were found to be within the acceptable limit. Conclusions This technique was successfully tested with UPLC-MS to confirm the chemical structures of newly formed degradation products of Bempedoic acid and Ezetimibe and stress studies as per ICH Q2 (R1) guidelines.